DA'WAH VALUES IN THE MARSIALAPARI TRADITION OF THE MANDAILING COMMUNITY IN GONTING PEGE VILLAGE, TAPANULI SELATAN REGENCY - Ritonga, Riskiya Ruksah; Sahrul, Sahrul (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study aims to identify the da'wah values embedded within the Marsialapari culture practiced in Gonting Pege Village, Aek Bilah District, Tapanuli Selatan Regency. Marsialapari is a mutual cooperation tradition among the Mandailing community, primarily practiced during rice planting and harvesting activities. This study employs a qualitative method with an ethnographic approach, using observation, in depth interviews, and documentation as data collection techniques. Informants included a traditional leader, a religious leader, a Marsialapari practitioner, a village government official, and a youth participant. The findings reveal that Marsialapari culture embodies five interrelated da'wah values, namely ukhuwah or brotherhood, at ta'awun or mutual assistance, ikhlas or sincerity, amanah or trustworthiness and responsibility, and silaturahmi or the maintenance of social ties, each of which is reinforced through relevant verses of the Quran and hadith of the Prophet. Despite significant social change driven by agricultural technology and wage based labor systems, the Gonting Pege community continues to preserve this tradition, which simultaneously strengthens social relationships and family bonds. These findings indicate that Marsialapari functions as a form of da'wah bil hal, or da'wah through action, integrating Islamic teachings into daily life without displacing the local wisdom passed down across generations. This study contributes to the broader discourse on local culture based da'wah in Indonesia and underscores the importance of preserving such traditions amid ongoing modernization.